2002
DOI: 10.1038/sj.cgt.7700508
|View full text |Cite
|
Sign up to set email alerts
|

Procathepsin D in breast cancer: What do we know? Effects of ribozymes and other inhibitors

Abstract: Procathepsin D (pCD) is a major secreted glycoprotein in some human breast and other cancer cell lines. Several groups proposed that pCD served as a growth factor for these cell lines. Secreted pCD has been demonstrated in tissue section, tissue culture supernatants, carcinoma cytosols, and nipple aspirates. Moreover, several clinical studies suggested a potential role for this molecule in metastasis because its concentration in primary tumors correlated with an increased incidence of tumor metastases. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 67 publications
3
36
1
1
Order By: Relevance
“…33 In contrast, our earlier study and a study conducted by Couissi et al, had shown that secreted pCD had a direct effect on the invasive potential of cells. 5,32 Our present result, therefore, is in accordance with these studies where inhibition of pCD secretion significantly affected the invasive potential of cells. Thus, targeted downregulation of pCD by RNAi resulted in changes of MDA-MB-231 cells with reversion to a less invasive phenotype.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…33 In contrast, our earlier study and a study conducted by Couissi et al, had shown that secreted pCD had a direct effect on the invasive potential of cells. 5,32 Our present result, therefore, is in accordance with these studies where inhibition of pCD secretion significantly affected the invasive potential of cells. Thus, targeted downregulation of pCD by RNAi resulted in changes of MDA-MB-231 cells with reversion to a less invasive phenotype.…”
Section: Discussionsupporting
confidence: 83%
“…Targeting pCD with antibodies, hammerhead ribozymes and antisense oligonucleotides has been earlier reported. 32,33 Recently, a synthetic siRNA sequence against CD was used in normal cell to determine the role of CD in apoptosis. 34 As individual siRNAs targeted to different regions of a transcript display striking differences in efficacy and specificity, [35][36][37] we designed three siRNA sequences against the entire length of pCD mRNA to obtain maximum silencing.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous experiments using synthetic AP, anti-AP antibodies or mutant pCD with deleted AP, we demonstrated that AP itself stimulates growth of breast, prostate and lung cancer cells in vitro and in vivo [180,182,183,185,186,190,191,199,200]. Although the mitogenic effect of AP was not confirmed by Glondu et al under their experimental conditions [194], Bazzet et al independently demonstrated mitogenicity of AP in ovarian cancer cells [184].…”
Section: Cancer Cell Proliferationmentioning
confidence: 84%
“…Sivaparvathi et al observed that anti-CD antibody inhbited glioblastoma cell invasion through Matrigel [206]. In our experimental conditions, genetic manipulation with the amount of pCD secreted by breast and lung cancer cells strongly influences their ability to cross Matrigel membrane in vitro as well as their metastatic potential in vivo [186,188,189,199]. Invasive capacity in vitro was also stimulated by overexpression of pCD in CD-deficient fibroblasts [27].…”
Section: Invasion and Metastasismentioning
confidence: 97%
See 1 more Smart Citation